Simulation of the shading pattern of periodically pruned trees in agroforestry systems - Nygren, Pekka (Pesquisa Agropecuaria Brasileira, 1993)
One of the main difficulties in the development of agroforestry systems research is the size and high cost of experiments which cover an adequate range of arrangements of trees and crops. One solution to this problem is to use simulation models to explore a wide range of designs and test only the best in the field. The present article presents a simulation model for the shading pattern of periodically pruned trees. The model permits to estimate the photosynthetic photon exposure during a user defined time in a field with trees once the location and dimensions of the trees, the crop height, geographical latitude and atmospheric transmittance are known. The field is divided into 50 x 50 cm squares and simulation is realized independently for all of them. The model includes the canopy transmittance parameters only for Erythrina poeppigiana (Walpers) O.F. Cook, but modifying these parameters the model could be applied for any agroforestry tree species managed with periodic prunings. The main application of the model is to explore theoretically the effect of the trees on the radiation regime above the crop in agroforestry systems.
Keywords: competence for solar radiation; design of agroforestry systems; Erythrina poeppigiana; tree geometry; photosynthetic photon exposure (PPE); photosynthetically active radiation